Theoretical Assumptions and Validation of a Scale for International Comparative Research on Teachers' Attitudes Toward Educating Talented Students - Teresa Giza (Ignatianum University Press, 2022)
The aim of the research was to construct a scale of teachers' attitudes toward the education of gifted students that could identify the types and predictors of attitudes. The research was prompted by the current lack of tools with good psychometric parameters. A questionnaire was prepared for the needs of an international comparative study on teachers (N = 630) from six Central and Eastern European countries: Belarus, Bulgaria, Poland, Romania, Slovakia, and Ukraine. The theoretical models of giftedness and empirical data both indicated the important role teachers play in the development of students' giftedness. The teachers' characteristics were somewhat ambiguous. The article describes the assumptions, construction stages, and validation results of the questionnaire, which contained 64 statements (items) selected from a wide range of opinions after thorough substantive and linguistic consultations. The fundamental descriptive statistics for each item were analyzed. The final selection of items occurred as a result of confirmatory factor analysis, which did not demonstrate sufficient fit between the questionnaire's theoretical structure and the data. Exploratory factor analysis, on the other hand, allowed for the version of the questionnaire with a three-factor structure to be adopted. Three types of attitudes were identified regarding gifted students' education: one expressing a negative attitude and two positive ones. As a result of the validation, a scale of attitudes was created with appropriate psychometric characteristics, consisting of 33 items. Further studies are being conducted to interpret the three dimensions of the scale and the variables that differentiate them.